Hormonal mechanisms underlying termination of larval diapause by juvenile hormone in the bamboo borer, Omphisa fuscidentalis - Tippawan Singtripop (2018)
Topical application of methoprene, a juvenile hormone analogue (JHA), induces pupation by activating the prothoracic glands (PGs) in diapausing larvae of the bamboo borer, Omphisa fuscidentalis. To determine the minimum stimulation period for PG activation, we transplanted PGs of JHA-treated larvae (donors) into non-treated larvae (recipients) on successive days after JHA treatment and observed the recipients for pupation. JHA stimulation for 1 day was sufficient to induce pupation. In recipient larvae, the hemolymph ecdysteroid titer increased transiently on day 18 after transplantation and significantly on days 24-28, prior to pupation. Secretory activity of recipient PGs increased transiently on day 16 and days 22-28. Because the recipient PG activity was too low to account for an increased ecdysteroid titer, the JHA-stimulated donor PGs must produce the major part of hemolymph ecdysteroids. In addition, the ecdysteroid produced by the donor PGs might have stimulated the recipient PGs. We examined the possible involvement of two ecdysone receptor (EcR) isoforms, OfEcR-A and OfEcR-B1, in PG activation by JHA, and found that although both isoforms were up-regulated, accompanied by an increased ecdysteroid titer in the hemolymph, the isoform mRNA levels were not altered at all before the increase in PG secretory activity. Thus, EcR expression might not be involved in feedback activation of PGs. © 2007 Elsevier Ltd. All rights reserved.